2015
DOI: 10.1016/j.virusres.2015.02.025
|View full text |Cite
|
Sign up to set email alerts
|

The structure and functions of coronavirus genomic 3′ and 5′ ends

Abstract: Coronaviruses (CoVs) are an important cause of illness in humans and animals. Most human coronaviruses commonly cause relatively mild respiratory illnesses; however two zoonotic coronaviruses, SARS-CoV and MERS-CoV, can cause severe illness and death. Investigations over the past thirty-five years have illuminated many aspects of coronavirus replication. The focus of this review is the functional analysis of conserved RNA secondary structures in the 5’ and 3’ of the betacoronavirus genomes. The 5’ 350 nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
509
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(530 citation statements)
references
References 148 publications
(326 reference statements)
18
509
0
3
Order By: Relevance
“…BCoV is an enveloped plus strand RNA virus that belongs to the https://doi.org/10. 1016 T genus Betacoronavirus (Yang and Leibowitz, 2015;Oma et al, 2016;Pfefferle et al, 2009). While different strains may have some antigenic variability, all strains elicit cross-reactive seropositivity and thus form a single serotype (Clark, 1993;El-Ghorr et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…BCoV is an enveloped plus strand RNA virus that belongs to the https://doi.org/10. 1016 T genus Betacoronavirus (Yang and Leibowitz, 2015;Oma et al, 2016;Pfefferle et al, 2009). While different strains may have some antigenic variability, all strains elicit cross-reactive seropositivity and thus form a single serotype (Clark, 1993;El-Ghorr et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of multiple of these elements is supported by bioinformatics (conservation), biochemical probing, and site-directed mutagenesis. For an overview of the structure and function of the RNA elements that have been implicated in CoV or AV replication and transcription, the reader is referred to detailed reviews that have been published elsewhere (Madhugiri et al, 2016;Masters, 2007;Sola et al, 2011;Yang and Leibowitz, 2015). However, it has remained largely unclear whether these elements interact with the RdRp domain-containing subunit directly or with other components of the RTC, as for example reported by Züst et al who observed that second-site mutations in the small nsp8 and nsp9 subunits of the RTC could compensate for mutations in conserved RNA sequences near the genomic 3 end of the murine hepatitis coronavirus (MHV) genome (Züst et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The first isolation of BоCV from bronchial secretion and nasopharyngeal washings of calves with signs of pneumonia occurred in 1982 and later, it was determined as bovine respiratory coronavirus (BRCoV) [1,2] . Strains isolated from diarrhoeic newborn calves and cattle have been classified as enteric or enteropathogenic coronaviruses (BECoV) [3] . Тhomas et al [4] affirmed that enteric and respiratory BCoV were the same, although detected in different life cycle stages.…”
Section: Introductionmentioning
confidence: 99%
“…Тhomas et al [4] affirmed that enteric and respiratory BCoV were the same, although detected in different life cycle stages. They have been isolated from the intestines and lung of calves affected with pneumoenteritis syndrome, and were antigenically and genomically similar [3,4] .…”
Section: Introductionmentioning
confidence: 99%